Application For Marriage Dispensation For Underage Pregnant Women Post The Application Of Law Number 16 Of 2019 Concerning Amendment To Law Number 1 Of 1974 Concerning Marriage - Djunastuti, Erni; Alhadiansyah, Alhadiansyah; Susila, Sugeng; Marnita, Marnita; Tahir, Muhammad (UNIVERSITAS PAKUAN, 2022)
In essence, everything in this world God created in pairs, as well as humans. Nowadays, teenagers are very easily influenced by their friends and fall into promiscuity, in which they commit acts that are prohibited by religion and violate religious norms. This causes a lot of negative things for them, one of which is pregnancy outside of marriage, so that early marriage occurs. Early marriages that have not reached the age of 19 years can request dispensation from marriage to the Office of Religious Affairs and the Office of the Religious Courts. Marriage dispensation is a relief given by the court to prospective husbands or wives who wish to carry out a marriage, where the age of one or both of the prospective brides has not yet reached the age limit stipulated in Law Number 16 of 2019 concerning Amendments to the Law. Law Number 1 of 1974 Concerning Marriage. The problem in this study is